Toward institutional transformation: warming the chilly climate for women in STEM through macrostructural change - Erichsen, Kristen; Šaras, Emily D.; Perez-Felkner, Lara (Frontiers in Education, 2024)
Although the demand for graduates with Science, Technology, Engineering, and Mathematics (STEM) credentials continues to climb, women remain underrepresented as both students and faculty in STEM higher education. Compounding social forces can hinder organizational change for gender equity in STEM, constraining institutions and individuals within them. This study advances Blau's (1977) macrostructural theory to examine the impact of gender composition (including group size and heterogeneity) of women faculty on structural change, as measured by gender desegregation of STEM degree earners. We advance this theory by incorporating faculty rank, rather than treating group composition as a static category. This study draws on a federal repository of data to assess institutional change in the share of STEM women faculty in the U.S.We employ quasi-experimental methods to explore the following research questions: (1) does hiring more women onto an institution's faculty roster shrink the gender gap among STEM degree earners? and (2) does segregation of faculty by gender within institutions shape the gender gap among STEM degree earners? While institutional efforts herald their efforts of hiring more women faculty, our findings indicate that gender desegregation of STEM degree earners partially depends on the promotion of women faculty to tenure.